Victims of Bullying: Emotion Recognition and Understanding - Franzen, Minita; de Jong, Peter J.; Veling, Wim; aan het Rot, Marije (Frontiers in Psychology, 2021)
Introduction: Victims of bullying often show interpersonal problems, such as having less high quality interpersonal relationships compared to non-involved individuals. Research suggests that interpersonal struggles are associated with diminished emotional intelligence and competence and can lead to mental health problems such as depression. Therefore, we examined emotion recognition abilities, empathic accuracy, and behavioural responses to emotions in bullying victims and non-involved individuals. Based on previous research, we expected victims to show diminished skills in all three domains. Methods: Adolescents (Mage=17 years; 67% female; no “other” gender participants) with (N=24) and without (N=21) a self-reported history of bullying victimisation in high school completed a Virtual Reality facial emotion recognition task, an empathic accuracy task using videos of people recounting real-life autobiographical events, and a computer task in which they indicated their likely behavioural responses to facial emotions. Results: The two groups only significantly differed in recognising emotions when taking their depression symptoms into account. Across emotions, victims had a lower recognition accuracy than non-involved individuals. When examining emotion-specific differences, victims showed lower accuracy for neutral faces which they mainly mistook for angry faces. Conclusions: In contrast to expectations, adolescents with a high-school history of bullying victimisation mostly showed similar emotional intelligence and competence skills as non-involved individuals. Nonetheless we found some subtle differences regarding emotion recognition. Victims misjudged neutral as angry faces. This suggests a hostile attribution bias which might help explain victims’ interpersonal problems as well as their increased risk for mental health problems.